Ligand-induced changes in the conformational dynamics of a bacterial cytotoxic endonuclease. - van den Bremer, E; Keeble, A; Visser, A; van Hoek, A; Kleanthous, K; Heck, A; Jiskoot, W (2004)
Knowledge about the conformational dynamics of a protein is key to understanding its biochemical and biophysical properties. In the present work we investigated the dynamic properties of the enzymatic domain of DNase colicins via time-resolved fluorescence and anisotropy decay analysis in combination with steady-state acrylamide quenching experiments. The dynamic properties of the apoenzyme were compared to those of the E9 DNase ligated to the transition metal ion Zn(2+) and the natural inhibitor Im9. We further investigated the contributions of each of the two tryptophans within the E9 DNase (Trp22 and Trp58) using two single-tryptophan mutants (E9 W22F and E9 W58F). Wild-type E9 DNase, E9 W22F, and E9 W58F, as well as Im9, showed multiple lifetime decays. The time-resolved and steady-state fluorescence results indicated that complexation of E9 DNase with Zn(2+) induces compaction of the E9 DNase structure, accompanied by immobilization of Trp22 along with a reduced solvent accessibility for both tryptophans. Im9 binding resulted in immobilization of Trp22 along with a decrease in the longest lifetime component. In contrast, Trp58 experienced less restriction on complexation of E9 DNase with Im9 and showed an increase in the longest lifetime component. Furthermore, the results point out that the Im9-induced changes in the conformational dynamics of E9 DNase are predominant and occur independently of the Zn(2+)-induced conformational effects.